Antisite occupation induced single anionic redox chemistry and structural stabilization of layered sodium chromium sulfide - Shadike, Zulipiya; Zhou, Yong-Ning; Chen, Lan-Li; Wu, Qu; Yue, Ji-Li; Zhang, Nian; Yang, Xiao-Qing; Gu, Lin; Liu, Xiao-Song; Shi, Si-Qi; Fu, Zheng-Wen (Nature communications, 2017)
The intercalation compounds with various electrochemically active or inactive elements in the layered structure have been the subject of increasing interest due to their high capacities, good reversibility, simple structures, and ease of synthesis. However, their reversible intercalation/deintercalation redox chemistries in previous compounds involve a single cationic redox reaction or a cumulative cationic and anionic redox reaction. Here we report an anionic redox chemistry and structural stabilization of layered sodium chromium sulfide. It was discovered that the sulfur in sodium chromium sulfide is electrochemically active, undergoing oxidation/reduction rather than chromium. Significantly, sodium ions can successfully move out and into without changing its lattice parameter c , which is explained in terms of the occurrence of chromium/sodium vacancy antisite during desodiation and sodiation processes. Our present work not only enriches the electrochemistry of layered intercalation compounds, but also extends the scope of investigation on high-capacity electrodes. The rational design of intercalation electrodes is largely confined to the optimization of redox chemistry of transition metals and oxygen. Here, the authors report the single anionic redox process in NaCrS 2 where it is sulfur rather than chromium that works as the electrochemical active species.